Agent-based simulation for market diffusion of passenger cars and motorcycles BEV in Greater Jakarta Area - Rizqi Ilma Nugroho; Till Gnann; Daniel Speth; Widodo Wahyu Purwanto; Jessica Hanafi; Sutanto Soehodho (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2024)
Battery electric vehicles (BEV) present a promising approach to decarbonizing the transportation sector. This extends beyond electric passenger cars, such as electric motorcycles that hold significant potential in emerging markets with high population density and income disparities. However, providing access to infrastructure remains a challenge in increasing BEV adoption. This research endeavours to determine BEV passenger cars (BEV-PC) and motorcycles (BEV-MC) market diffusion within an emerging market city, focusing on the Greater Jakarta Area, utilizing an Agent-Based Model that considers charging infrastructure availability. Findings indicate that BEV-PC diffusion could attain about 9% of the total vehicle stock by 2030 and almost 75% by 2050 under the Current Policy. Similarly, BEV-MC adoption rates may reach 39% by 2030 and 80% by 2050. Introducing a vehicle purchase subsidy along with full abolishment of fossil fuel subsidies could amplify the diffusion of BEV-PC and BEV-MC to almost triple and double in 2030, respectively.
Keywords: 330; Battery electric vehicles (BEV); BEV passenger cars (BEV-PC); BEV motorcycles (BEV-MC)